The specter of resurging communicable disease epidemics - Richard Tjan (Universa Medicina, 2012)
In developing countries there still are differentials in immunization coverage between regions, such as in Indonesia for measles vaccination between urban and rural regions, as reported in 2007.(1) Therefore, it may not be surprising to hear about local or even national outbreaks of communicable disease in these countries. However, that an epidemic should occur in developed nations with relatively complete immunization coverage, comes somewhat as a surprise. The epidemic referred to is the whooping-cough epidemic occurring this year in the USA, and on a smaller scale in Europe, particularly in the UK.